LEGAL ANALYSIS OF WITNESS TESTIMONIUM DE AUDITU’S POSITION ON DECISION NO. 115/PID.SUS/2021/PN.KTG: Case Study on Constitutional Court Decision No. 65/PUU-Vlll/2010 - Mbewa, Adelina; Haryadi, Wahyu Tris (jfpublisher, 2023)
Testmonium de audito has not been accepted as evidence under the Criminal Procedure Code because its authenticity has not been tested. Under the Constitutional Court’s decision No.65/PUU-VIII/2010, testimonium de audito is considered as evidence, and can be used in both criminal and civil cases. Therefore, this research is conducted to determine the witness's position in the trial and verdict Number 115/Pid.Sus/2021/PN.Ktg. The case study of Kotamobagu District Court Decision Number 115/Pid.Sus/2021/PN.Ktg and Law No. 8/1981 on the Criminal Procedure Code become the basis of normative legal research methodology in this research, which also used primary and secondary sources. The findings of this research indicate that in Constitutional Court Decision No.65/PUU-VIII/2010, law enforcers should agree that witnesses who actually see, hear, or suffer a criminal event are not always required. On the other hand, Testimonium de Auditu witnesses cannot be used as independent witnesses in the case of Decision No. 115/Pid.Sus/2021/PN.Ktg because it does not include the requirements of the witnesses required.